PENYULUHAN KESEHATAN REPRODUKSI PADA REMAJA DI DESA RIDAN PERMAI - Zurrahmi Z.R; Putri Eka Sudiarti; Rizki Rahmawati Lestari (Universitas Pahlawan Tuanku Tambusai, 2022)
Adolescence or odelesence is a dynamic growth and development phase in an individual's life. Ridan Permai Village is one of the villages in the working area of ??the Bangkinang Public Health Center, Kampar Regency. When a survey was conducted by the team for the head of Ridan Permai Village, it was found that adolescents rarely receive reproductive health counseling, reproductive health checks and other activities that can support the reproductive health status of adolescents. Adolescents are also a group that is vulnerable and at risk of experiencing various reproductive health problems and behavioral deviations in a negative direction because they are still in the search for identity phase. Based on the situation analysis and problem identification mentioned above, a problem can be formulated, namely the need for reproductive health counseling for adolescents in Ridan Permai Village. The implementation method used in this activity is in the form of counseling on reproductive health for adolescents. This activity took place in Ridan Permai Village on August 18 2022. The result of this community service is that it can increase adolescent knowledge about reproductive health and the status of adolescent reproductive health is monitored and has increased. It is also hoped that this activity will not end in service activities, but can form cooperation in disseminating information about reproductive health and other public health issues in improving public health status in general. Keywords: Reproductive Health, Adolescents